Analisis Risiko Cedera Lutut pada Lompat Smash Bulu Tangkis - Revi Meyrdiansyah Fatma; Fajar Awang Irawan (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to analyse the risk of knee injury during the landing phase of the jumping smash movement in athletes from the CPLUSco Badminton Club in Semarang. The jumping smash is a highly explosive and effective attacking technique in the game, but it carries a high risk of injury, particularly to the knee joint due to the pressure exerted during landing. Materials and Methods. This study employed a quantitative descriptive method with a sample of 10 male athletes aged 14–18 years, selected using purposive sampling. Data were collected through motion capture using a Sony A6000 camera and analysed using Kinovea software version 0.9.5. The primary focus of the study was the landing phase, with biomechanical indicators including landing time (s), right and left knee flexion angles (°), and inter-leg distance during landing (cm). Results. This study found that the optimal landing duration was in the range of 0.20–0.36 seconds, but there was a mismatch in knee angle and foot position, which was a significant risk factor for knee injury. Conclusion. The conclusion of this study found that biomechanical evaluation needs to be conducted regularly to reduce the risk of injury.